The relationship between coaches’ leadership styles and athletes’ burnout among UiTM Perlis athletes / Faiz Najmuddin Kamarul Bahrain ... [et al.] - Kamarul Bahrain, Faiz Najmuddin; Mohd Kassim, Ahmad Fikri; Ismail, Ahmad Dzulkarnain; Mohd Rosli, Norfaezah; Jamaludin, Masshera; Mansor, Siti Hannariah (Universiti Teknologi MARA, Perlis, 2024)
Burnout among athletes can be influenced by many factors and one of the most significant factors that influence athletes towards burnout is the leadership involved in their particular sports. Thus, the purpose of this study is to identify the preferred coaches’ leadership styles, levels of athletes’ burnout, and to investigate the relationship between coaches’ leadership styles and athletes’ burnout among UiTM Perlis athletes. A total of 164 athletes (85 males and 79 females) participated in this study. The Revised Leadership Scale for Sport and the Athlete Burnout Questionnaire were used to collect data. Further, the data were analysed by using means and standard deviation of each item. Meanwhile, the Pearson Correlation Coefficient was used to investigate the relationship between coaches’ leadership styles and athletes’ burnout. Statistical significance was set at p < .05. Results revealed that positive feedback was the most preferred coaches’ leadership styles among UiTM Perlis athletes (M = 4.24, SD = .54). Results also showed that the overall score for burnout among athletes was considered low to moderate (M = 2.52, SD = .70). Pearson correlation test showed that there was a significant relationship between coaches’ leadership styles of autocratic behaviour (r = .385, p = .001), training and instruction (r = -.269, p = .001), positive feedback (r = -.295, p = .001), situational consideration (r = -.217, p = .005) and athletes’ burnout. Thus, this finding revealed that when coaches provided more training and instruction, more positive feedback, more situational consideration, and less autocratic behaviour tend to be associated with lower levels of burnout among athletes due to the expertise of coaches that could influence the athletes’ psychological well-being.